The Effects of Go Training with Scaffolding for Enhancing Executive Functions in Undergraduate Students - Tajaroensuk, Mati; Apichartkriangkrai, Chanapat; Jirasophin , Lapon (Ratchaphruek Journal, 2025)
This study aimed to 1) compare the Executive Function (EF) of students in the experimental group before and after participating in a Go training program, and 2) compare the EF of students in the experimental and control groups after completing the program. This quasi-experimental research involved a sample of 50 undergraduate students from a private higher education institution enrolled in a Go course. The sample was selected using a multi-stage sampling method and divided into an experimental group and a control group, with 25 students in each. The research instruments included a Go training program consisting of 10 practice sessions and an Executive Function assessment form comprising 32 items, which evaluated six EF components. The assessment demonstrated discrimination power ranging from .21 to .87 and a reliability coefficient of .95. Data were analyzed using mean, standard deviation, paired-sample t-tests, and independent-sample t-tests. The findings revealed that 1) After the intervention, the experimental group showed statistically significant improvements in EF scores compared to the pre-test phase, particularly in Focusing, Planning, and overall EF at the .05 level, with Initiation improving at the .01 level, and 2) Post-test results showed that the experimental group outperformed the control group in EF scores, with statistically significant differences at the .05 level, especially in Focusing and Planning skills. These findings suggest that the Go training program effectively enhances executive functioning among undergraduate students.